Exploring the epidemiology of suicide attempts: Risk modeling in Kermanshah—Iran - Khademi, Nahid; Zangeneh, Alireza; Ziapour, Arash; Saeidi, Shahram; Teimouri, Raziyeh; Yenneti, Komali; Moghadam, Shahrzad; Almasi, Ali; Golanbari, Shirin Zardui (Frontiers in Public Health, 2022)
Background: Suicide attempt is a serious global public health issue. The patterns of suicide may vary depending on the individual characteristics, methods, causes, and the geographical area. This study identifies the spatial patterns of suicide attempts in Kermanshah province, Iran. Method: The sample size of this cross-sectional study is 18331 people (7234 males and 11097 females) who attempted suicide in Kermanshah province between 2006 and 2014. Data was collected from the records of patients referred to the emergency department of hospitals in Kermanshah and analysed using tests of Mean Center, Standard Distance, and Average Nearest Neighbour. Out of the 18,331 cases, 74% attempted suicide with drug overdose, 13% with toxins and pesticides, 0.59% with chemicals, 4% with fire, 1% by self-immolation, 1% by hanging, 0.16% with firearms and 0.7% with cold weapons. The spatial pattern of all suicide attempts in Kermanshah was clustered (Z-score <- 2.58). Results: The results of the mean center and standard distance tests show that drug overdose, poisoning with toxins and pesticides, and chemicals mostly were used in the central areas of Kermanshah province. The mean center of suicide attempts by self-immolation, hanging and firearms was in the western parts of the province, while the suicide attempts with narcotic drug were concentrated in the eastern regions of the province. Conclusion: The results of this study show that the methods of suicide attempt vary with geographical areas in the province. Therefore, it is suggested that planning tailored to the geographical location can reduce suicide attempts in Kermanshah.